RNAmod: an integrated system for the annotation of mRNA modifications - Liu, Qi; Gregory, Richard I (Nucleic acids research, 2019)
Dynamic and reversible RNA modifications such as N6-methyladenosine (m6A) can play important roles in regulating messenger RNA (mRNA) splicing, export, stability and translation. Defective mRNA modification through altered expression of the methyltransferase and/or demethylases results in developmental defects and cancer progression. Identifying modified mRNAs, annotating the distribution of modification sites across the mRNA, as well as characterizing and comparing other modification features are essential for studying the function and elucidating the mechanism of mRNA modifications. Several methods including methylated RNA immunoprecipitation and sequencing (MeRIP-seq) are available for the detection of mRNA modifications. However, a convenient and comprehensive tool to annotate diverse kinds of mRNA modifications in different species is lacking. Here, we developed RNAmod (https://bioinformatics.sc.cn/RNAmod), an interactive, one-stop, web-based platform for the automated analysis, annotation, and visualization of mRNA modifications in 21 species. RNAmod provides intuitive interfaces to show outputs including the distribution of RNA modifications, modification coverage for different gene features, functional annotation of modified mRNAs, and comparisons between different groups or specific gene sets. Furthermore, sites of known RNA modification, as well as binding site data for hundreds of RNA-binding proteins (RBPs) are integrated in RNAmod to help users compare their modification data with known modifications and to explore the relationship with the binding sites of known RBPs. RNAmod is freely available and meets the emerging need for a convenient and comprehensive analysis tool for the fast-developing RNA modification field.